Potential and Comparative Tablet Disintegrant Properties of Pectin Obtained from Five Okra Genotypes in Ghana - Frederick William Akuffo Owusu; Mariam El Boakye-Gyasi; Jacob Kwaku Agbenorhevi; Marcel Tunkumgnen Bayor; Kwabena Ofori-Kwakye (Scientifica)
Okra pectin has been studied as a potential excipient in tablet formulations for pharmaceutical industries. Okra is widely grown and available in Ghana and other parts of the world. The prospective use of pectin from okra genotypes grown in Ghana as tablet disintegrants has not been reported. This study aims to determine the potential and comparative disintegrating properties of pectin from five okra genotypes (Abelmoschus esculentus L.) in Ghana using uncoated immediate release paracetamol tablet formulations. The yield of the pectin from the various genotypes ranged between 6.12 and 18.84% w/w. The extracted pectins had pH ranging from slightly acidic to almost neutral (6.39–6.92). Pectin from the various genotypes exhibited good swelling indexes (˃200%), varying solubility in different solvents, and low moisture content (˂20%). Elemental analysis of the extracted pectin from the various genotypes revealed very low levels of toxic metals and micronutrients. Pectin from the various genotypes was evaluated as disintegrants within concentrations of 5–10% w/w (F1–F18). Their disintegrating properties were compared to that of maize starch BP. All the formulated batches of uncoated immediate release paracetamol tablets (F1–F18) passed the following: uniformity of weight test, uniformity of dimensions, hardness, friability (˂1%), and drug content (95–105%). Significant differences (p≤0.05) were observed between the hardness of the maize starch tablets and tablets formulated from pectin of the various genotypes. Pectin from all genotypes other than PC5 exhibited good disintegrating properties (DT ˂ 15 min) and subsequently passed the dissolution profile test (≥70% release in 45 minutes). Tablets formulated with PC5 as disintegrants at all concentrations (5% w/w (F5), 7.5% w/w (F11), and 10% w/w (F17)) failed the disintegration and dissolution tests. Ultimately, pectins extracted from PC1, PC2, PC3, and PC4 can be commercially exploited as disintegrants in immediate release tablets.